A multiparametric CFD analysis of multiphase annular flows for oil and gas drilling applications. (2nd November 2017) - Epelle, Emmanuel I.; Gerogiorgis, Dimitrios I.
Graphical abstract: Highlights: A multi-parametric CFD analysis of multiphase (solid–liquid) annular flows has been performed. Cuttings concentration, pressure drop, axial fluid/solid velocities are the key state variables studied. Drill pipe eccentricity, inclination, rotation, rate of penetration (ROP) and rheology widely varied. Fluid velocity, well inclination and eccentricity emerge as pivotal for cuttings transport efficiency. An extensive literature experimental data compilation is used for validation (relative error <11%). Abstract: The increasing global energy demand has pushed the oil industry towards developing more innovative and advanced methods of enhancing oil recovery even under unfavourable technical and environmental conditions. The severity of many operational problems affecting the drilling and production of oil and gas wells is worsened by inaccessibility; hence, remedial efforts must be implemented from afar. One of these problems is ensuring efficient removal of formation rock cuttings with a suitable fluid whose rheology is often complicated. Furthermore, pressure losses along the annular geometry involved, and decreased rates of penetration (ROP) due to accumulated drill cuttings downhole, constitute significant portions of the total energy to be supplied. Thus, the application of sophisticated modelling techniques with credible elucidation of the phase distributions (solids, liquids and gas) and prevalent flow regimes becomes essential, if adequate and economic design of a drilling program is desired. The advent of computational fluid dynamics (CFD) and the growth in the available computational power to support it have provided an unprecedented opportunity to simulate and understand complex real flows, especially when experimental methods become extremely demanding. The present study employs the tool of computational fluid dynamics to simulate a two-phase solid–liquid flow in an annulus based on the analysis of cuttings concentration, pressure drop profiles, axial fluid, and solid velocities as a function of several drilling parameters: drill pipe eccentricity, inclination, drill pipe rotation, ROP and fluid rheology. Special emphasis is however placed on the impact of changing hole eccentricity on cuttings transport efficiency. The suitability of the Eulerian–Eulerian (EE) multiphase tracking scheme in modelling systems of high volume fractions is fully utilised in this work. A non-Newtonian (power law) fluid model with well-described flow parameters is implemented, considering a uniform cuttings size distribution (3 mm). A commercial CFD software (ANSYS FLUENT™ 17.1) has been used; the descriptive and predictive potential of the CFD software has been confirmed on account of the reasonable agreement with previously published experimental data (a relative error of less than 11% is achieved), as illustrated by the corresponding sensitivity plots. This multi-parametric CFD analysis study of multiphase cutting transport during drilling applications has confirmed that fluid velocity, hole inclination and annular eccentricity are the most influential factors governing the cuttings transport efficiency.